Tratamento de efluente de indústria alimentícia por processos físico-químicos e biológicos - Peralta, Aline Hanny (2014)
The losses caused by the action of man has reached large proportions and can be observed mainly by changes in water quality. Food industry need this resource to use in various ways that goes from the incorporation of the products to washing of utensils manufacturing. This paper studies improvements to the treatment of effluent from a food company for a launch within the standards required by law. The research was divided into two stages; the first consisted in the physical-chemical treatment with the proposed use of two tips of coagulants: aluminum sulfate (with the aid of flocculent GAP) and plant-base coagulant tannin (Tanfloc SG). The second stage of the treatment was based on the evaluation of three different biological treatment systems, two submerged aerated biofilters (BAS), (reactor 1 and reactor 2) and an activated sludge reactor (reactor 3). In reactors 1 and 3 were added nutrients to help the oxidation of organic compounds. In the first stage of treatment with the use of coagulant of aluminum sulfate a 29% removal of COD, 76% removal of color and 72% removal of turbidity was obtained. When using natural tannin-based coagulant results were 14% removal of COD, 88% removal of color and 83% removal of turbidity. In biological reactors, it was verified that the reactor 1, in which nutrients were inserted, removal of all variables were higher (44% removal of COD, 31% removal of color, 67% removal of turbidity). By the end of the study it was decided to conduct the physical-chemical tests of final effluent from three biological reactors again in order to achieve improved yields. As optimal results with the use of aluminum sulfate values of 80% removal of color, 89% removal of turbidity and 43% removal of COD were achieved. When using natural tannin-based coagulant the optimal results achieved were 85% removal of color and turbidity and 48% removal of COD. In conclusion in the case of the effluent analyzed, with high concentration of organic matter, the use of biological treatment subsequent to physical-chemical treatment is necessary for the retention of biomass and suspended solids derived from BAS. The addition of nutrients has significant BAS efficiency compared to other reactors analyzed, so this practice also becomes interesting as an aid to achieving the parameters required by law to disposal of effluent into water bodies.